Students' Mathematical Communication Ability and Disposition in The Implementation of Micro Didactic Design at Junior High School - Hidayu Sulisti; Sugiatno Sugiatno; Silvia Sayu (JETL (Journal of Education, Teaching and Learning), 2018)
The reasons for conducting this research are that some teachers have taken inappropriate learning strategies and that students’ mathematical disposition and mathematical communication ability in learning are still low. The Didactical Design Research (DDR) method begins with preliminary study on 28 eighth graders (junior high schoolers), aiming at exploring the students’ learning obstacles to develop a micro didactic design. This micro didactic design is then implemented to the same students, after being subjected to validation process. The research results indicate that the learning using micro didactic design can minimize students’ learning obstacles and this, eventually, positively contributes to students’ mathematical communication ability and disposition in materi algebraic factorization. From the data analysis results, it is found that the price of effect size for micro didactic design learning on mathematical communication ability is 1.07, and from Table Z it is found that its contribution is 35.77%. Meanwhile, the price of effect size for micro didactic design learning on mathematical disposition is 0.2, and from Table Z it is found that its contribution is 7.93%.